(untitled) (Global Journal of Science Frontier Research, 2014)
Synthesis of superheavy nuclei has been achieved recently through hot fusion reactions. A systematic theoretical calculation of determining the stability of the superheavy nucleus Z=114 is studied in the context of angular momentum and temperature. The level density can provide clues to the applicability of the statistical model which is only correct for a high density of excited states. The collapse of pairing correlation at moderately higher spin and at low temperature causes a shape change and stability at higher spin is also expected. The drop in separation energy is closely associated with the structural changes in the rotating nuclei; relative increase in neutron emission probability around certain values of temperature may be construed as evidence for the shape transition. Such effects are not obtained for 298 114. Hence this statistical study reveals a higher stability for 298 114 against temperature and angular momentum.